A novel method for the establishment of autologous skin cell suspensions: characterisation of cellular sub-populations, epidermal stem cell content and wound response-enhancing biological properties - Peake, Michael; Dunnill, Chris; Ibraheem, Khalidah; Smith, Adrian; Clarke, Douglas J.; Georgopoulos, Nikolaos T. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction. Autologous cell suspension (ACS)-based therapy represents a highly promising approach for burns and chronic wounds. However, existing technologies have not achieved the desired clinical success due to several limitations. To overcome practical and cost-associated obstacles of existing ACS methods, we have established a novel methodology for rapid, enzymatic disaggregation of human skin cells and their isolation using a procedure that requires no specialist laboratory instrumentation and is performed at room temperature. Methods. Cells were isolated using enzymatic disaggregation of split-thickness human skin followed by several filtration steps for isolation of cell populations, and cell viability was determined. Individual population recovery was confirmed in appropriate culture medium types, and the presence of epidermal stem cells (EpSCs) within keratinocyte sub-populations was defined by flow cytometry via detection of CD49 and CD71. Positive mediators of wound healing secreted by ACS-derived cultures established on a collagen-based wound-bed mimic were detected by proteome arrays and quantified by ELISA, and the role of such mediators was determined by cell proliferation assays. The effect of ACS-derived conditioned-medium on myofibroblasts was investigated using an in-vitro model of myofibroblast differentiation via detection of α-SMA using immunoblotting and immunofluorescence microscopy. Results. Our methodology permitted efficient recovery of keratinocytes, fibroblasts and melanocytes, which remained viable upon long-term culture. ACS-derivatives comprised sub-populations with the CD49-high/CD71-low expression profile known to demarcate EpSCs. Via secretion of mitogenic factors and wound healing-enhancing mediators, the ACS secretome accelerated keratinocyte proliferation and markedly curtailed cytodifferentiation of myofibroblasts, the latter being key mediators of fibrosis and scarring. Discussion. The systematic characterisation of the cell types within our ACS isolates provided evidence for their superior cell viability and the presence of EpSCs that are critical drivers of wound healing. We defined the biological properties of ACS-derived keratinocytes, which include ability to secrete positive mediators of wound healing as well as suppression of myofibroblast cytodifferentiation. Thus, our study provides several lines of evidence that the established ACS isolates comprise highly-viable cell populations which can physically support wound healing and possess biological properties that have the potential to enhance not only the speed but also the quality of wound healing.